2019
DOI: 10.1016/j.cattod.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight photoactivity of rice husks-derived biogenic silica

Abstract: Carbon-containing SiO 2-based photocatalysts were prepared by the solvothermal treatment of rice husk as biogenic precursor in the presence and absence of TiO 2 and used for the photocatalytic degradation of rhodamine-B under simulated solar light. Data showed that the prepared catalysts are mainly composed of biogenic silica and displayed mesoporous character with surface areas ranging from 65 to 174 m 2 g-1. The obtained materials showed photocatalytic activity comparable to that of commercial TiO 2-P25 powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
1
25
0
2
Order By: Relevance
“…e FTIR transmission spectrum of rice husk ( C�C bonds in organic components [15], respectively. e bands at 1745 cm −1 and 1660 cm −1 are also related to the elastic vibrations of the CO bond in carboxyl groups [16].…”
Section: Results Of Ft-ir Analysismentioning
confidence: 99%
“…e FTIR transmission spectrum of rice husk ( C�C bonds in organic components [15], respectively. e bands at 1745 cm −1 and 1660 cm −1 are also related to the elastic vibrations of the CO bond in carboxyl groups [16].…”
Section: Results Of Ft-ir Analysismentioning
confidence: 99%
“…Hiện nay, trấu được dùng để sấy lúa, sản xuất củi trấu, bán cho các lò gạch, sử dụng trong đun nấu tại các cơ sở tiểu thủ công nghiệp và hộ gia đình... Tuy nhiên, lượng sử dụng này khá nhỏ so với lượng phát sinh hàng năm đặc biệt là vùng đồng bằng sông Cửu Long [4]. Thành phần nguyên tố chính của trấu gồm có C (65,13%), N (1,87%), O (28,51%) và Si (4,48%) [5]. Do đó khi đốt trấu làm phát sinh khói, bụi và các chất khí góp phần gây ô nhiễm môi trường không khí và sức khoẻ con người đặc biệt khi hầu hết các vị trí đốt nằm cạnh nhà máy xay xát trong khu cân cư.…”
Section: đặT Vấn đềunclassified
“…Các nghiên cứu cho thấy khi đốt sinh khối, có đến 90% các bon được giải phóng vào khí quyển tạo thành CO và CO 2 , ít hơn 5% các bon được giải phóng tồn tại trong các hạt bụi [6,7]. Ngoài các chất thải trên, khí polycyclic aromatic hydrocarbons (PAHs) cũng được phát hiện trong quá trình đốt sinh khối [5][6][7][8][9][10]. Myanma, Thái Lan, Campuchia và Việt Nam là những quốc gia đóng góp lượng phát thải nhiều nhất từ quá trình đốt sinh khối [11,12].…”
Section: đặT Vấn đềunclassified
“…A possible way to avoid this issue is to apply materials with higher surface area as support for the active phase (TiO 2 ). In this perspective, silica (SiO 2 ) has properties that make it attractive as it is chemically inert, thermally stable, transparent to UV irradiation and presents high surface area (Bellardita et al 2010;de Cordoba et al 2019). Results observed by .…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the presence of SiO 2 promotes the substrate pre-concentration on the surface of the material, which results in higher accessibility to photoexcited TiO 2 present on the surface of the photocatalyst (Anderson and Bard, 1997). Several researchers have carried out studies of the application of composite materials (TiO 2 /SiO 2 ) in photocatalytic processes, especially for the degradation of organic substances (Yamashita et al, 1998;Hu et al, 2003;Malinowska et al, 2003;Chen et al, 2004;Zhang et al, 2006;Marugán et al, 2007;Wilhelm and Stephan, 2007;Lee et al, 2008;Maldotti et al, 2008;Bellardita et al, 2010;Matos et al, 2018;de Cordoba et al, 2019). Wilhelm and Stephan (2007) performed the synthesis of nano-spheres SiO 2 @TiO 2 by heterocoagulation.…”
Section: Introductionmentioning
confidence: 99%